Distributed predictive formation control of networked mobile robots subject to communication delay - Hosseinzadeh Yamchi, Mohammad; Mahboobi Esfanjani, Reza (Robotics and autonomous systems, 2017)
This paper provides a novel distributed predictive controller with guaranteed stability to maintain formation between mobile robots during their motion along a desired path and assure no collisions with obstacles or other adjacent robots, while data is exchanged among them via a packet-delaying communication network. First, the closed-loop system dynamics are described as a delayed differential equation with tunable parameters. Then, these adjustable gains are determined synchronously in each agent by the proposed predictive strategy such that a desirable formation is achieved. The efficiency and applicability of the suggested scheme are demonstrated by simulation results.